2011
DOI: 10.3354/meps09029
|View full text |Cite
|
Sign up to set email alerts
|

Benthic macroinvertebrate functional diversity regulates nutrient and algal dynamics in a shallow estuary

Abstract: Proliferation of macroalgal blooms is regulated by grazing pressure and nutrient availability, which may be mediated directly by benthic macroinvertebrates or indirectly through feedback mechanisms. Using invertebrates common to a shallow estuary in Cape Cod, Massachusetts (USA), we determined effects of faunal diversity on benthic microalgae, net ecosystem metabolism, sediment nutrient fluxes, and macroalgal biomass and productivity. Laboratory microcosms contained sediments with single-and mixed-species inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 58 publications
0
22
0
1
Order By: Relevance
“…En ambientes acuáticos la mayor cantidad de trabajos relacionados con la diversidad funcional se ha desarrollado en macro-invertebrados riparios (Heino, 2005(Heino, , 2008Heino et al, 2007 con el enfoque hacia el análisis de los atributos funcionales), así como en zonas costeras de sustrato rocoso (Crowe & Russel, 2009;Clemente et al, 2010), fondos blandos (Pacheco et al, 2011) y estuarios (Villéger et al, 2008McLenaghan et al, 2011).…”
Section: La Diversidad Funcional En Ambientes Marinosunclassified
“…En ambientes acuáticos la mayor cantidad de trabajos relacionados con la diversidad funcional se ha desarrollado en macro-invertebrados riparios (Heino, 2005(Heino, , 2008Heino et al, 2007 con el enfoque hacia el análisis de los atributos funcionales), así como en zonas costeras de sustrato rocoso (Crowe & Russel, 2009;Clemente et al, 2010), fondos blandos (Pacheco et al, 2011) y estuarios (Villéger et al, 2008McLenaghan et al, 2011).…”
Section: La Diversidad Funcional En Ambientes Marinosunclassified
“…High densities of some macroinvertebrates have been observed in association with bloom forming macroalgae (Fong et al, 1997;Guidone et al, 2010), and it has been recently suggested that these numerous herbivores may be facilitating blooms rather than simply opportunistically grazing on the abundant macroalgal biomass (Guidone et al, 2010(Guidone et al, , 2012McLenaghan et al, 2011). There is a body of research that suggests herbivore facilitation of macroalgal blooms might be possible since grazers can have the paradoxical effect of enhancing growth of macroalgae under equilibrium (non-bloom) conditions by three possible mechanisms.…”
Section: Introductionmentioning
confidence: 97%
“…Second, herbivores may facilitate macroalgae by selectively grazing on the epiphytes that would otherwise compete with macroalgae for nutrients and light (Duffy, 1990;Guidone et al, 2010;Raberg and Kautsky, 2008). Finally, in soft-bottomed environments, surface depositfeeding gastropods can impact nutrient cycling, benthic microalgae, and oxygenation of surface sediment (Ieno et al, 2006;McLenaghan et al, 2011;Pillay et al, 2009;Premo, 2011;Weerman et al, 2011). By removing benthic microalgae, "bull-dozing" sediments, or otherwise altering the redox status at the sediment surface, snails can promote benthic-pelagic coupling by increasing the efflux of N mineralized in the sediments to the water column where it is presumably available for uptake by macroalgae (Ieno et al, 2006;McLenaghan et al, 2011;Raffaelli, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sediment reworking through ophiuroid bioturbation also contributes to sediment biochemical processes (Lohrer et al 2004, Webb & Eyre 2004, McLenaghan et al 2011. Because of its high densities and its mobility and burrowing activity within the superficial sediment layers, Ophiocomina nigra is likely to locally affect nutrient cycling at the sediment surface and ultimately modify the associated benthic assemblages.…”
Section: Ecological Consequences Of Changes In Ophiuroid Densitiesmentioning
confidence: 99%